Pengungkapan Tanggung Jawab Sosial Terstandarisasi, Kredibilitas Manajemen, dan Manajemen Laba - Santoso, Eko Budi; Basuki, Basuki; Isnalita, Isnalita (E-Jurnal Akuntansi, 2023)
This study aims to examine the effect of standardized social responsibility disclosure on earnings management and the role of management credibility in this relationship. The research sample is a company going public in the non-financial sector on the Indonesia Stock Exchange that has disclosed GRI-based social responsibility for the 2013-2019 period. The analysis technique used in this study is moderated regression analysis (MRA). The results of the study found that disclosure of social responsibility has a negative effect on earnings management and management credibility strengthens this relationship. The results of the study indicate that companies that put more effort into disclosing their social responsibility through standardized disclosures will reduce earnings management practices and this is reinforced by the existence of a credible management team. The novelty of this study lies in the use of a comprehensive index in measuring social responsibility disclosure which is a combination of aspects of accountability and performance, as well as the formulation of management credibility measurements. Keywords: Corporate Social Responsibility; Earnings Management; Management Credibility